Functional and Structural MR Imaging in Neuropsychiatric Disorders, Part 2: Application in Schizophrenia and Autism - Mueller, S.; Keeser, D.; Reiser, M.F.; Teipel, S.; Meindl, T. (American Journal of Neuroradiology, 2012)
SUMMARY: During the past decade, the application of advanced MR imaging techniques in neuropsychiatric disorders has seen a rapid increase. Disease-specific alterations in brain function can be assessed by fMRI. Structural GM and WM properties are increasingly investigated by DTI and voxel-based approaches like VBM. These methods provide neurobiologic correlates for brain architecture and function, evaluation tools for therapeutic approaches, and potential early markers for diagnosis. Having provided insight into principles of functional and structural imaging and delineated common findings in mild cognitive impairment and Alzheimer disease in Part 1 of this review, we will now focus on autism and schizophrenia as common psychiatric disorders covering different stages of the life span. This review concludes by summarizing current applications, limitations, and future prospects in the field of MR imaging−based neuroimaging. ACCanterior cingulate cortexASDautism spectrum disordersBOLDblood oxygen level–dependentDMNdefault mode networkDSMDiagnostic and Statistical Manual of Mental DisordersFAfractional anisotropyGMgray matterHFAhigh-functioning autismICDInternational Classification of DiseasesRSNresting-state networkrsfMRIresting-state fMRIVBMvoxel-based morphometry